The Fulfilment of Tax Obligation in Case of Slovenian Tax Residents Working in Other Countries - Jagrič, Timotej; Lešnik, Tomaž; O. Grbenic, Stefan; Jagrič, Vita (Naše gospodarstvo/Our economy, 2019)
We study the impact of selected characteristics of Slovenian tax residents with income from work with source in other countries on their fulfilment of tax obligations from this income. We received anonymised data for the year 2015 from Slovenian Financial administration, which includes selected taxation data, some demographic variables as well as some data from other registers. On the sample of 9016 taxpayers of personal income tax from the group with income from work with source in other countries we found that with knowledge of some characteristics of taxpayers it is possible to discern a higher or lower probability of fulfilment of their tax obligations. Tools as the here presented model can help to increase the effectiveness of targeted inspection taxation supervision. The analysis has shown that groups of taxpayers with common characteristics share also a common pattern of the fulfilment of their tax obligations.